Carl Junker, Zum Buchwesen in Österreich Gesammelte Schriften (1896-1927) - Hall, Murray Gordon (Edition Praesens, 2001)
Anyone interested in the history of the book in Austria will, sooner rather than later, come across the publications of Carl Junker (1864-1928). No one before or after him has done as much toward compiling what we know today about the history of the book, whether it be in the Austro-Hungarian Monarchy or in the Republic of Austria. As far as the signifcance of his writings is concerned, it is entirely fitting to quote the words Junker himself wrote regarding the official book trade publication, "Österreichisch-ungarische Buchhändler-Correspondenz", which appeared from 1860: "The 50 voumes which we now have-no matter what negative opinion some people might hold of their contents-represent, for the future historian dealing with the history of our book trade, a standard work, which he will have to continually consult." With his studies on the Austrian book trade or publishing trade, as the case may be, Carl Junker made a contribution which even today, more than seventy years after his death, defies comparison. The state of research reflected in his articles and lengthier studies, his monographs, is, in most cases, the same as it is today. Archival material which he had at his disposal and which he used as the basis for his studies is no longer available today. Thus, his documentations have, in many respects, become "primary sources" in their own right. His text "Die Katastrophe in Wien", for example, is an authentic report on the loss of irreplacable archival records from the "Staatsarchiv des Innern und der Justiz", stored in the Palace of Justice which went up in flames in 1927. The losses included censorship and police records from the reign of Joseph 11 and records pertaining to the newspaper trade. As Junker reports, little was left. The volume of Junker's collected writings contains all of his book publications, including monographs of firms such as Gerold, Hölder-Pichler-Tempsky and Friedrich Jasper as well as his critical analysis of the state of copyright protection in Austria-Hungary at the turn of the century, not to mention his pioneering publication on Austrian press history (the likes of which has not been published since.) As the collection of Junker's writings shows, he was also very much interested in developments in bibliography, as, for example, decimal classification in libraries. Junker also wrote histories of two trade organizations in Austria, the 'Verein der österreichisch- ungarischen Buch- Kunst- und Musikalienhändler" (1899) and the -Korporation der Wiener Buch-, Kunst- und Musikalienhändler" (1907). Both works contain information (e.g. legislation governing the book trade) essential to today's book scholars. But the current volume also makes other historical topics easily accessible to us today. There are articles about the reorganisation of the Austrian book trade after World War One, articles he wrote articles for countless exhibition catalogues. And although some of his works were commissioned, Junker shows on repeated occasions that he is by no means uncritical. Junker died in 1928 before he could complete one last major work, namely a history of book publishing companies in Austria. What he did leave behind is contained in this volume and can provide the basis for scholars today to try to match his diligence. A compilation of this kind will invariably be used as a reference work, and in order to make the incredible wealth of information easily accessible, there are five indices: company names, personal names, subject, place names and magazines and newspapers.